2004
DOI: 10.1007/bf03325077
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Eating Attitudes Test: A study of Mexican eating disorders patients

Abstract: This study provides evidence that the Mexican version of the EAT is an economical, reliable and potentially useful instrument for research in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 14 publications
3
29
0
9
Order By: Relevance
“…49,50 However, placement in the ''at-risk'' category should still be interpreted with some caution. The specificity of the EAT-40 varies with the sample being tested, with some studies finding the EAT-40 to have low false positive rates for eating disorders and other research questioning its specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 However, placement in the ''at-risk'' category should still be interpreted with some caution. The specificity of the EAT-40 varies with the sample being tested, with some studies finding the EAT-40 to have low false positive rates for eating disorders and other research questioning its specificity.…”
Section: Resultsmentioning
confidence: 99%
“…48 The EAT-40 also has been shown to differentiate between eating disorder patients and non-patients in a Mexico City sample. 49,50 The current study utilized a more conservative cutoff score of 30 to indicate significant eating concerns, despite some evidence that a slightly lower cutoff score of 28 may be appropriate with Mexican female samples. 49,50 The reliability of this measure with the current sample was adequate (Cronbach's alpha of 0.83).…”
Section: Figure Ratingmentioning
confidence: 99%
“…EAT-26 is one of the most widely used self-report measures for evaluating eating attitudes and behaviors. Several studies demonstrated acceptable factor structure, concurrent validity, and reliability of various versions of the EAT-26 among Western cultures (32,33). Nobakht and Dezhkam (34) reported satisfactory internal consistency and test-retest reliability among adolescent Iranian girls.…”
Section: Research Toolsmentioning
confidence: 99%
“…Al momento de su construcción (Garner & Garfinkel, 1979) se obtuvo una confiabilidad de .79 para las mujeres anoréxicas y de .94 para la muestra total. Según su validación en población mexicana (Álvarez-Rayón et al, 2004), el instrumento evalúa cinco dimensiones: Restricción alimentaria (α=.88), Bulimia (α=.87), Impulso hacia la delgadez (α=.85), Preocupación por la comida (α=.77) y Presión social percibida (α=.76).…”
Section: ) Appearance Schemas Inventory-revised (Asi-r)unclassified